Clinical Significance and Potential Role of LSM4 Overexpression in Hepatocellular Carcinoma: An Integrated Analysis Based on Multiple Databases - Chen, Liang; Lin, Yun-hua; Liu, Guo-qing; Huang, Jing-en; Wei, Wei; Yang, Zhong-hua; Hu, Yi-ming; Xie, Jia-heng; Yu, Hong-zhu (Frontiers in Genetics, 2022)
Background: Hepatocellular carcinoma (HCC) is a solid tumor with high recurrence rate and high mortality. It is crucial to discover available biomarkers to achieve early diagnosis and improve the prognosis. The effect of LSM4 in HCC still remains unrevealed. Our study is dedicated to exploring the expression of LSM4 in HCC, demonstrating its clinical significance and potential molecular mechanisms. Methods: Clinical information and LSM4 expression values of HCC were obtained from GEO and TCGA databases. Survival analysis and receiver operating characteristic (ROC) curve analysis were applied to evaluate the prognostic and diagnostic significance of LSM4. Calculating pooled standardized mean difference (SMD) and performing summary receiver operating characteristic (sROC) curve analysis to further determine its expression status and diagnostic significance. LSM4-related co-expressed genes (CEGs) were obtained and explored their clinical significance in HCC. LSM4-associated pathways were identified through Gene set enrichment analysis (GSEA). Results: Up-regulated LSM4 was detected in HCC tissues (SMD = 1.56, 95% CI: 1.29-1.84) and overexpressed LSM4 had excellent distinguishing ability (AUC= 0.91, 95% CI: 0.88-0.93). LSM4 was associated with clinical stage, tumor grade, and lymph node metastasis status (p<0.05). Survival analysis showed that high LSM4 expression was related to poor overall survival (OS) of HCC patients. Cox regression analysis suggested that high LSM4 expression may be an independent risk factor for HCC. We obtained 9 up-regulated CEGs of LSM4 in HCC tissues, and 6 CEGs had good prognostic and diagnostic significance. GSEA analysis showed that up-regulated LSM4 was closely related to the cell cycle, cell replication, focal adhesion, and several metabolism-associated pathways, including fatty acid metabolism. Conclusion: Overexpressed LSM4 serves as a promising diagnostic and prognostic biomarker of HCC. Besides, LSM4 may play a synergistic effect with CEGs in promoting the growth and metastasis of HCC cells via regulating crucial pathways such as cell cycle, focal adhesion, and metabolism-associated pathways.